2000
DOI: 10.1159/000026678
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the EEG of Abstinent Cocaine Abusers

Abstract: Gender differences in the EEG were explored in cocaine-abusing individuals not seeking treatment. Twenty currently abstinent cocaine-abusing females aged 21–41 were studied. Their cocaine use history was matched to 20 currently abstinent cocaine-abusing males. Twelve female and 20 male non-drug-abusing individuals served as a control group. Resting eyes closed EEG was recorded from 8 leads. The males who used cocaine had elevated EEG beta (p < 0.0125) and reduced alpha (p < 0.0125) when compared to the cocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…The theta findings are similar to other published studies. 20,24,25,27 The finding of decreased beta power appears inconsistent with prior findings from this laboratory 28,30 and others showing increased beta power among cocaine users. 26 This may be due to different analytic techniques or to differences in subject gender, alcohol use, or prevalence of anti-social personality disorder or family history of alcoholism, all of which have been associated with changes in beta power.…”
Section: Discussioncontrasting
confidence: 80%
“…The theta findings are similar to other published studies. 20,24,25,27 The finding of decreased beta power appears inconsistent with prior findings from this laboratory 28,30 and others showing increased beta power among cocaine users. 26 This may be due to different analytic techniques or to differences in subject gender, alcohol use, or prevalence of anti-social personality disorder or family history of alcoholism, all of which have been associated with changes in beta power.…”
Section: Discussioncontrasting
confidence: 80%
“…Compared to sexmatched controls, male cocaine-dependent subjects showed a higher frequency of frontal "defects" (56%) than did female cocaine-dependent subjects (0%). Similarly, King et al 47 found that whereas the electroencephalogram (EEG) of male cocaine-dependent subjects significantly differed from controls, the EEG of female cocaine-dependent subjects did not differ from sex-matched controls. Female cocaine-dependent subjects also showed less neuronal injury and glial activation in the frontal cortex compared with their male counterparts.14 Sex differences between cocaine-dependent men and women may result from premorbid differences or the menstrual/estrous-related pharmacokinetic48 or pharmacodynamic48 -51 effects of cocaine.…”
Section: Discussionmentioning
confidence: 93%
“…We matched cocaine-using and control subjects for gender, which had been done in only 3 of 7 previous cross-sectional studies. 11,12,14 Gender can have a significant influence on EEG power in cocaine users. 12 Although the mean age of our 2 groups differed significantly (35.9 [3.5] versus 25.1 [3.1]), all subjects were between 20 and 39 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,14 Gender can have a significant influence on EEG power in cocaine users. 12 Although the mean age of our 2 groups differed significantly (35.9 [3.5] versus 25.1 [3.1]), all subjects were between 20 and 39 years of age. EEG power does not vary significantly within this age range; age 40 is considered to be a general cutoff between the EEG of "younger" patients and "older" patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation